1996
DOI: 10.1177/070674379604100106
|View full text |Cite
|
Sign up to set email alerts
|

Premorbid and Postmorbid School Functioning in Bipolar Adolescents: Description and Suggested Academic Interventions

Abstract: Onset of bipolar illness in adolescence negatively impacts on the teenager's ability to function effectively in the school environment. Specific program modifications are required in order to optimize the bipolar teenager's success at school. These are identified and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 25 publications
1
42
0
Order By: Relevance
“…There is some evidence that the level of scholastic achievement attained at school by people with BD is higher than that of the general population (Coryell et al, 1993;Quackenbush et al, 1996). For example, in one study conducted in New Zealand, McPherson and associates (1992) found that people with BD were statistically more likely to have passed school certification than people from the local community.…”
Section: Under-achieved Vocational Statusmentioning
confidence: 92%
“…There is some evidence that the level of scholastic achievement attained at school by people with BD is higher than that of the general population (Coryell et al, 1993;Quackenbush et al, 1996). For example, in one study conducted in New Zealand, McPherson and associates (1992) found that people with BD were statistically more likely to have passed school certification than people from the local community.…”
Section: Under-achieved Vocational Statusmentioning
confidence: 92%
“…The few existing neuropsychological studies of at-risk children from our laboratory and others have identified significant discrepancies between Verbal and Performance IQ (VIQ > PIQ; Decina et al, 1983;Kestenbaum, 1979;McDonoughRyan et al, 2002), deficiencies in academic achievement (McDonough-Ryan et al, 2002;Quakenbush, Kutcher, Robertson, Boulos, & Chaban, 1996;Sigurdsson, Fombonne, Sayal, & Checkley, 1999), and attentional disturbance (Kron & Kestenbaum, 1988). Consistent with these findings in at-risk children, it has been reported that a small group (N ¼ 7) of unaffected monozygotic twins of adults with BPD were deficient in short-term memory and mental control (Gourovitch et al, 1999).…”
mentioning
confidence: 93%
“…4.1 . In line with this, the retrospective investigations and record reviews suggest that children who later develop BD exhibit good academic functioning prior to illness onset (Quackenbush et al 1996 ;Kutcher et al 1998 ;Uzelac et al 2006 ;Reichenberg et al 2002 ;Toulopoulou et al 2006 ).…”
Section: Long-term Development Of the Neurocognitive Deficitmentioning
confidence: 81%
“…The overall neuropsychological defi cit has been associated with earlier age at onset (Osuji and Cullum 2005 ). Immediately following illness onset, adolescents with BD exhibit signifi cant deterioration in cognitive and social domains (Quackenbush et al 1996 ). Similarly, in adults, it has been reported that the defi cit is present already during the fi rst mood episode (Nehra et al 2006 ).…”
Section: Long-term Development Of the Neurocognitive Deficitmentioning
confidence: 98%